The association between blood coagulation activity and lung function: a population-based study. - Andrew W Fogarty; Sarah A Lewis; Tricia M McKeever; Gordon D O Lowe; Lorna Clark; John Britton (PLoS ONE, 2010)
BACKGROUND: Increased in susceptibility to thrombotic disease may be associated with lower lung function. If causal, this association may suggest an area for development of new interventions for lung disease. The aim of this study was to investigate the association between blood coagulation activation as measured by plasma d-dimers and lung function. METHODOLOGY/PRINCIPAL FINDINGS: We conducted a cross-sectional study on 2463 randomly selected adults in 1991 and followed up 1252 of these individuals in 2000. Plasma D-dimer levels, a marker of activity of blood coagulation pathways, were analysed in the baseline 1991 samples. There was an inverse cross-sectional association between plasma D-dimer and Forced Expiratory Volume in one second, with a decrease of 71 ml per µg FEU/ml increment in plasma D-dimer (95% confidence intervals CI: -135 to -6), and a decrease in Forced Vital Capacity (97 ml per µg FEU/ml increase in D-dimer, 95%CI: -170 to -24). These associations were attenuated after adjustment for serum highly sensitive CRP. No association was observed between plasma D-dimer and the decline in lung function between 1991 and 2000. CONCLUSIONS/SIGNIFICANCE: The cross-sectional findings are consistent with the hypothesis that activation of blood coagulation pathways is associated with decreased lung function, and that systemic inflammation may contribute to this relation. However, the lack of an association with decline in lung function suggests that clotting pathways that involve d-dimers may not be a promising therapeutic target for new interventions for respiratory disease.